THE PRAGMATISM OF TAX REMITTANCE AND THE PROBLEM OF PENSION PROVISION FOR LABOR MIGRANTS IN UKRAINE (INNOVATIVE ECONOMY, 2020)
Onyschuk V.O. THE PRAGMATISM OF TAX REMITTANCE AND THE PROBLEM OF PENSION PROVISION FOR LABOR MIGRANTS IN UKRAINEPurpose. The aim of the article is the analysis of theoretical and legal aspects and the development of practical recommendations for the taxation of remittances and the improvement of the system of social protection and pensions of Ukrainian labor migrants.Methodology of research. The theoretical and methodological basis of the research is the scientific works of domestic and foreign scientists, normative and legislative acts of Ukraine on taxation, social and pension provision of labor migrants, international cooperation. General scientific methods are used in the process of work: analysis and synthesis, comparison – in the study of current practice of taxation of remittances of labor migrants and the identification of problems of pension and social security of labor migrants; the logical method – for theoretical generalizations and the formation of the findings of the study.Findings. It has been established that in domestic practice, the tax remittance of labor migrants has no clear mechanism for its implementation. The insufficient protection of Ukrainian labor migrants in foreign labor markets and narrow “places” of international cooperation in the aspect of employment of Ukrainian citizens are revealed. Problematic aspects in the field of pension provision for labor migrants have been identified and investigated, as well as measures have been proposed to address these issues and ensure proper social protection of labor migrants.Originality. The contradictory nature of domestic legislation in the field of taxation of money transfers of labor migrants is revealed. The necessity of state support of labor migrants has been substantiated and proved. Measures and instruments for improving the system of social protection and pension provision for labor migrants in Ukraine are proposed.Practical value. The obtained results of the research will promote optimization of tax legislation in the aspect of taxation of remittances of labor migrants, increasing efficiency of implementation of international cooperation in matters of social and pension protection of labor migrants.Key words: labor migrants; money transfers of labor migrants; taxation of money transfers from individuals from abroad; pension provision for labor migrants; social security of labor migrants.
Keywords: Key words; labor migrants; money transfers of labor migrants; taxation of money transfers from individuals from abroad; pension provision for labor migrants; social security of labor migrants.